The effect of the meditation based mandala programme on distress, anxiety and depression in the caregivers of cancer patients in palliative care unit - KARABUĞA YAKAR, HATİCE (My University, 2023)
Mental health problems were found to be more common than physical health problems in cancer caregivers in palliative care units. This is a quasi-experimental study planned to determine the effect of the meditation based mandala programme on distress, anxiety and depression in caregivers of cancer patients in a palliative care unit. Planned as a single-group pre-test/post-test design, with a total of 11 caregivers. Data were collected with the Caregiver Diagnosis Form, Distress Thermometer, Beck Depression Inventory, and Beck Anxiety Inventory. Caregivers participated in the Meditation Based Mandala Programme once a week, which lasted 2 hours for 5 weeks. The distress, depression and anxiety levels of the patients were measured before the programme started and at the end of the programme. Meditation based mandala programme is effective in reducing the distress, depression and anxiety levels of caregivers of cancer patients in the palliative care unit.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Sosyal ve Beşeri Bilimler; Sosyoloji; Demografi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Social Sciences and Humanities; Sociology; Demography; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; YOĞUN BAKIM; KAMU, ÇEVRE VE İŞ SAĞLIĞI; DEMOGRAFİ; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; CRITICAL CARE MEDICINE; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; DEMOGRAPHY; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Yoğun Bakım Tıbbı; Yaşam Boyu ve Yaşam Boyu Çalışmaları; Health (social science); Social Sciences & Humanities; Critical Care and Intensive Care Medicine; Life-span and Life-course Studies; cancer; caregiver; mandala; palliative care